Dynamic Crop Planning for Enhancing the Crop Productivity Under Rainfed Conditions - Kothari, A K; Kumar, Virendra; Jain, P M; Purohit, R C (Journal of Agricultural Engineering, 2007)
Rainfall data of Bhilwara district in Rajasthan state for a period of 45 years were analysed from two approaches viz.; ’Meteorological’ approach and ’Onset of monsoon’ approach. The results revealed considerable difference in rainfall characteristics with respect to length of growing period, water surplus/ deficit and probability of intervening dry spells due to these approaches. The ’Onset of monsoon’ approach is more rational as it precisely describes the actual crop environment and provides information for varying onsets of monsoon as compared to ’Meteorological’ approach. The results of water balance study revealed an increase of 142.6% in water deficit due to delay in onset (31st SMW) as compared to normal onset of monsoon (27th SMW), whereas an increase of 35.2% and decrease of 33.7% in water surplus was recorded due to late and early onset of monsoon. The correlation studies also reveal that onset of monsoon is inversely correlated (-0.91) with duration of rainy season while positively correlated (0.83) with water deficit. Thus, the ’onset of monsoon’ approach should be considered for crop planning under rainfed regions to harness more profit per unit of rainfall.